Disaster, pre-emptive security and urban space in the post-9/11 New York City of Cloverfield and The Visitor. (1st March 2014) - Simon, Stephanie
Using two post-9/11 films set in New York City, Cloverfield (2008) and The Visitor (2008), this article interrogates the urban space of pre-emptive security practice in the United States. Putting these two films together, and tracing their characters' paths through the city, offers insights into the relationship between threat imaginaries, security practices and the complex cities within which they are interwoven. While pointing to some of the continuities with longer-standing socio-spatial tactics of urban control, this analysis also draws attention to the particular spatio-temporal landscape of pre-emption, which has come to define post-9/11 security stances. It is argued that pre-emptive security imaginaries and practices are stretched across urban spaces in ambiguous and uneven ways as attempts are made to render urban complexity, uncertainty and circulation visible and knowable. The cinematic paths of the characters in Cloverfield and The Visitor offer points of micro-visibility onto post-9/11 urban security practice as a circulatory process that is not ultimately fixed or fully competent. In this way the article complicates the imagination of a seamless, fully rendered urban battlespace and instead stresses the active process of securitizing potentialities and acts that slip in and out of the innumerable spatial stories that compose the urban fabric.